Pengaruh Kelengkungan Sudu Terhadap Kinerja Turbin Angin Savonius - Jamal, Jamal; Yunus, A. M. Shiddiq; Lewi, Lewi (Politeknik Negeri Ujung Pandang, 2019)
Savonius wind turbine is one of the wind turbines that is more widely used for low energy needs, with more energy needs, this turbine type is very feasible to be developed. This research aims to improve the performance of Savonius wind turbines with variations in turbine blade curvature and variations in wind speed. The research method is a laboratory experiment on the fan test, the blade curvature test variation is 1R; 1.5R and 2R, another variation is the wind speed which are 4.0; 5.5; 7.0 and 8.5 m/s. The experiement results shows that the greater the wind speed, the input power, air mass flow velocity, power output, and efficiency will be even greater; the greater the load force on the turbine shaft, the torque on the turbine shaft will also be greater; the relationship of force loads to power output and turbine efficiency is to construct a parabolic curve; for the same wind speed, the 2R turbine has the lowest rotation, power output and efficiency compared to the 1R and 1.5R turbines; at the same wind speed the 1R turbine produces a higher rotation but requires lower torque than the 1.5R turbine; at low wind speeds (4 m / s) the 1.5R turbine has better efficiency than the 1R turbine, whereas at the high wind speed (8.5 m/s) the 1R turbine has a better efficiency than the 1.5R turbine; The maximum efficiency is obtained at 89.56% in the 1R curvature turbine with a wind speed of 8.5 m / s.